Promoting the capacity for self-control in children: concepts and strategies in context - Chaverri Chaves, Pablo (2022)
This essay aims to show and discuss key aspects of child self-control based on recent research, as well as to propose factors and strategies to promote the development of this important capacity. To do this, he begins by defining self-control, then identifies some of its benefits, then describes the marshmallow test, as well as its analysis in context. Then it relates self-control with decision-making, analyzes the role of trust, the role of adults in its promotion in girls and boys, and finally proposes some strategies to support it.